Subsoiling before winter wheat alleviates the kernel position effect of densely grown summer maize by delaying post-silking root–shoot senescence - Lichao Zhai; Shijia Song; Lihua Zhang; Jinan Huang; Lihua Lü; Zhiqiang Dong; Yongzeng Cui; Mengjing Zheng; Wanbin Hou; Jingting Zhang; Yanrong Yao; Yanhong Cui; et al. (Journal of Integrative Agriculture)
The intensified kernel position effect is a common phenomenon in maize production under higher plant density, which limits crop productivity. Subsoiling is an effective agronomic practice for improving crop productivity. To clarify the effect of subsoiling before winter wheat on the kernel position effect of densely grown summer maize and its regulatory mechanism, field experiments were conducted during the 2020–2021 and 2021–2022 growing seasons using a split-plot design. The main plots included two tillage practices: conventional tillage practice (CT) and subsoiling before the sowing of winter wheat (SS); and the subplots consisted of three plant densities (D1–D3 at 6.0×104, 7.5×104, and 9.0×104 plants ha–1). Compared with CT, SS alleviated the kernel position effect by increasing the weight ratio of inferior to superior kernels (WR) in the D2 and D3 treated plants. The higher WR of SS treated plants contributed largely to the improved filling of inferior kernels. Under the same plant density, SS significantly improved the root dry matter accumulation (DMA) and antioxidant enzyme activities (superoxide dismutase (SOD) and peroxidase (POD)), and it reduced the malondialdehyde (MDA) content, especially for the plants grown under higher plant densities. These results indicated that SS delayed the root senescence, which is associated with the reduced soil bulk density. In addition, compared with CT, SS increased the leaf chlorophyll content from 20 days after silking to physiological maturity and the post-silking leaf area duration, and it reduced the post-silking leaf chlorophyll reduction rate and leaf area reduction rate, indicating that the post-silking leaf senescence had been alleviated. Under the same plant density, the post-silking DMA of SS was obviously higher than that of CT, which was probably related to the improved leaf area duration and photosynthetic enzyme activities (phosphoenolpyruvate carboxylase (PEPC) and Rubisco). The correlation analysis revealed that the main mechanism of SS in alleviating the kernel position effect of densely grown summer maize is as follows: SS delays the post-silking root–shoot senescence by regulating soil physical properties, and further improves the post-silking DMA and filling of inferior kernels, which ultimately alleviates the kernel position effect and improves grain yield. The results of this study provide new theoretical support for the promotion of summer maize yield by subsoiling before winter wheat.